Existence and Uniqueness of Solutions of Nonlinear Integral Equations Through Results in Fuzzy Bipolar Metric Spaces (Journal of Nonlinear Modeling and Analysis, 2025)
In this paper the concept of fuzzy bipolar metric spaces are investigated and their properties in relation with fixed points by the considerationof triangular property of fuzzy bipolar metric are explored. The study presentsa series of established results under covariant and contravariant mappings supported by illustrative examples and discusses the implications of these findings.Furthermore, the established results are applied to demonstrate the existenceand uniqueness of solutions to nonlinear integral equations. The exploration offuzzy bipolar metric spaces and their application to integral equations providesvaluable insights into the field of mathematical analysis and opens avenues forfurther research.
Keywords: Triangular property; fuzzy metric space; fuzzy bipolar metric space; covariant mappings; contravariant mappings.